GAS CHROMATOGRAPHY–MASS SPECTROSCOPY ANALYSIS OF ETHANOLIC EXTRACT OF LEAVES OF CORDIA OBLIQUA WILLD - SIVAKRISHNAN S; PRADEEPRAJ D (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Cordia obliqua Willd. also called as clammy cherry is a flowering plant species in the genus Cordia belonging to the family Boraginaceae. This study focus to find out the active principles and its therapeutic properties. Methods: C. obliqua was collected from B. Maduvangarai, Tamil Nadu, India. The leaves were collected and extract prepared from ethanol by hot continuous percolation method in Soxhlet apparatus for 24 h. The ethanolic extract was collected and analyzed using Perkin–Elmer gas chromatography–mass spectroscopy (GC–MS) for the identification of active biochemical constituents present in the leaves of C. obliqua Willd. Results: GC–MS analysis of the ethanolic extract of leaves of C. obliqua showed 11 bioactive compounds, the highest compound was named as 4-pentadecyne, 15-chloro-(13.574%) and lowest was named as 2-isopropyl-5-methylcyclohexyl 3-(1-(4-chlorophenyl)-3-oxobutyl)-coumarin-4-yl carbonate (6.461%). Conclusion: In the present study, we concluded that the phytochemical constituents of the ethanolic extract of leaves of C. obliqua by GC–MS is to furnish the scientific information to evolve potential phytomedicine.